Health care supply chain research: Where are we going? - Hokey Min (Logistics Research, 2017)
Led by the Obama administration, health-care laws, regulations, and policies have recently undergone dramatic changes with the hopes of improving universal access to quality health care. Such changes, however, pose unprecedented challenges of controlling ever-rising health care costs, while sustaining the high level of heath care services. To cope with these challenges, the health-care community and policy makers have long sought innovative solutions that can allow them to streamline health care practices and enhance productivity to the full potential. Though often overlooked in the past, an innovative solution that was increasingly put forward by many managerial experts is the adaptation of supply chain principles for health care that are designed to reduce wasteful spending, strengthen connectivity among health care partners, and increase visibility of needed care and resources. In an effort to help health care professionals add value to their systems, this paper traces the evolution of health care supply chain research, synthesizes the past and current research efforts to develop viable health care solutions and then proposes promising future research themes that can fine-tune these solutions.
Keywords: 650; health care; supply chain management; research synthesis; trend analysis